Differentiated Learning Integrated with Social Emotional Awareness and Digital Learning Media in Improving the Students Motivation and Learning Outcomes - Seri Amalia; Safrida S; Susi Mulia Ulva (Jurnal Penelitian Pendidikan IPA, 2024)
This learning is designed to facilitate the individual learning needs of different learners by integrating social and emotional awareness. The purpose of this research to improving the motivation and learning outcomes. This research uses the development of the ADDIE model. The results show an increase in student learning outcomes and student learning motivation in class XI IA2 SMA Negeri 1 Krueng Barona Jaya. Student learning outcomes with paired sample T-test test obtained sig. (2-tailed) 0.00 <0.05. Is a significant difference between biology learning outcomes in pre-test and post-test data. Students' responses through plasma membranes in class XI IA2 SMA Negeri 1 Krueng Barona Jaya is Very Good, with a percentage of 91.91%.